A multiscale XFEM approach to investigate the fracture behavior of bio-inspired composite materials. (15th May 2018) - Vellwock, Andre E.; Vergani, Laura; Libonati, Flavia
Abstract: In the setting of emerging approaches for material design, we investigate the use of the extended finite element method (XFEM) to predict the behavior of a newly designed bone-inspired fiber-reinforced composite and to elucidate the role of the characteristic microstructural features and interfaces on the overall fracture behavior. The outcome of the simulations, showing a good agreement with the experimental results, reveals the fundamental role played by the heterogeneous microstructure in altering the stress field, reducing the stress concentration at the crack tip, and the crucial role of the interface region ( i.e. cement line) in fostering the activation of characteristic toughening mechanisms, thus increasing the overall flaw tolerance of the composite. Graphical abstract: